Ansiedade pré competitiva e desempenho em atletas de ginástica artística feminina - Higor Alexandre Alves de Oliveira (2023)
Introduction: Women's artistic gymnastics (WAG) is a sport that requires high performance in physical and motor skills, with an emphasis on technical perfection across four apparatuses. Among these apparatuses, the floor exercise stands out as the only one that combines artistic demands with mandatory musical elements, resulting in a higher metabolic demand for the gymnasts. Given the sport's emphasis on concentration and the pursuit of perfection during routines, it is important to analyze somatic and cognitive anxiety, as well as self-confidence, particularly during competitions. Additionally, it is essential to examine influences that can be beneficial in this context, such as aerobic performance. Objective: This study aims to analyze the relationship between aerobic performance, body fat, and pre-competitive anxiety among gymnasts during their floor exercise routines. Methods: This descriptive study with a cross-sectional design was conducted using a non-probabilistic convenience sample of 12 WAG athletes, aged 9 to 12 years, from two training centers in Campo Grande, MS, Brazil. The athletes were divided into two groups based on their overall scores, with higher and lower performance, determined by combining aerobic performance with lower body fat percentages using the median as the cutoff point. Data collection involved administering questionnaires to the gymnasts to gather information on pre-competitive anxiety (CSAI-2R) and training details. Anthropometric and body composition assessments, as well as aerobic performance tests, were conducted. Results: The values for somatic anxiety in the higher and lower performance groups were 20.9±5.6 vs. 22.8±9.9, cognitive anxiety 24.3±5.27 vs. 23.3±7.7, and self-confidence 24.0±7.79 vs. 20.6±5.1. Regarding aerobic performance, the values for VO2max were 48.4±1.98 vs. 45.4±4.0 ml·min-1·kg-1, and the body fat percentage was 12±6.4 vs. 18.7±5.9%. Conclusion: Although no statistical differences were found between the groups and no correlations were observed among the variables, further studies are needed to investigate the factors that influence pre-competitive anxiety in WAG, as well as the impact of cardiorespiratory performance and body composition. Given the limited research addressing these aspects, recent studies on aerobic performance in this sport have gained significance.